A PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI PENGGUNAAN STRATEGI ACTIVE SHARING KNOWLEDGE UPAYA MEMPERSIAPKAN GENERASI ABAD 21: Berpikir Kritis - FERAZONA, SEPITA (Perspektif Pendidikan dan Keguruan, 2020)
This study aims to look at the Critical Thinking Ability Through the Use of Active Sharing Knowledge Strategies in an effort to prepare the 21st century generation of Material Excretion Systems. This research was conducted in April-July 2018/2019 Academic Year, at the Riau Islamic University, Faculty of Teacher Training and Education in Biology Study Program. The sample of this study consisted of one class, the determination of the sample by using purposive sampling technique. This type of research is a survey research with a qualitative approach. The method used in this research is experiment, which aims to find out a symptom or effect that arises, as a result of the existence of certain treatments. The data obtained were analyzed using quantitative data analysis techniques. The data obtained is the ability of students' critical thinking. The assessment of critical thinking abilities is carried out in accordance with the six indicators of critical thinking, namely: 1) Focus (focus), 2) Arguments (Reason), 3) Conclusions (inference), 4) Situation (Situation), 5) Clarity (Clarity), 6) Advanced Overview (Overview). The results showed that of the 17 critical thinking questions tested obtained a different presentation. 45% of the students' answers in the categories are very good and 55% are in the good categories. This proves that students' thinking on excretory material is good.